EKSISTENSI PRODI AKIDAH FILSAFAT DI FAKULTAS USHULUDDIN DAN HUMANIORA - Karim, Abdullah (UIN Ar-Raniry, 2014)
Philosophy of faith and Humanitiesdepartment is one of the important programs at the Faculty of Islamic Theology. In regard to the understanding and practicing of the true religion and avoid the deviation and the emergence of deviant teachings, the sciences that included at Philosophy of faith and Humanities department are the sciences which was very important to achieve the goal of study. The existence of Philosophy of faith and Humanities department is depend on students quantity, the competent provider and integral policy of the Indonesian Ministry of Religious Affairs. For that some policies should be initiated for strengthening of theologyfaculty existence.